Financial Performance Of Cement Industry In India – A Profitability Study (Journal of Namibian Studies : History Politics Culture, 2023)
Cement is a top priority construction material and hence is the fastest growing sector both worldwide and in India. India happens to rank the second in cement manufacture and consumption. India is a fast and rapid growing economy and has the largest growth potential to develop in the spheres of infrastructure and construction. Cement is the essence material for infrastructure development and hence the economic development of any economy. The Cement industry generates immense employment opportunities, directly and indirectly that is required for the development of under developed countries. Cement is the base material for all types of construction works, starting from smallest building to largest structures like dams and irrigation works. In India, cement industry is the prominent one where huge investments are made by both domestic and foreign investors. Cement industry in India is now heading towards achievement of global standards in production, safety and efficient use of energy. Another important target set for the cement industry in India is the sustainable development. The current study relates to the analysis of financial performance of select cement manufacturing companies in India with reference to Profitability using various profitability ratios. The study is restricted to three cement manufacturing companies, selected using certain criteria, for a period of five years ranging between 2018-19 to 2022-23. The study tends to reveal the performance efficiency of the selected companies with respect to its profitability position.